In irritable bowel syndrome, postprandial abdominal distention is associated with a reduction of intestinal tone. Issue 10 (3rd May 2017) - Di Stefano, M.; Bergonzi, M.; Miceli, E.; Klersy, C.; Pagani, E.; Corazza, G. R.
Abstract: Background: The pathophysiology of abdominal distention in irritable bowel syndrome (IBS) is still a matter of debate, but the relationship between modifications of intestinal tone and abdominal volume has never been analyzed. Methods: Eighty‐four patients affected by IBS and reporting moderate to severe abdominal distention were enrolled. Thirty‐nine presented abdominal distention immediately after and forty‐five presented abdominal distention independently of meal intake. Twenty healthy volunteers (HV), comparable for gender and age, were also enrolled. All the subjects underwent fasting and postprandial recto‐sigmoid volume monitoring with barostat and abdominal girth measurement to evaluate abdominal distention. Key Results: In comparison with HV (75±13 mL) and with patients with meal‐unrelated abdominal distention (135±56 mL), in the subgroup of patients with severe meal‐related abdominal distention recto‐sigmoid tone response to the meal was significantly reduced (mean increase of balloon volume 184±89 mL; P <.001), paralleling abdominal girth increase and occurring immediately after test meal intake. Meal‐induced abdominal girth modification was significantly correlated with meal‐related modification of recto‐sigmoid tone ( r =.71) and abdominal symptoms. Conclusions: In patients with IBS suffering from severe postprandial abdominal distention, a postprandial reduction of intestinal tone is associated with this bothersome symptom. Further studies are needed to evaluate whether drugs acting on the modification of intestinal tone could be useful in the treatment of these patients. Abstract : In the pathophysiology of abdominal distention the relationship between modifications of intestinal tone and abdominal volume has never been analyzed. In comparison with HVs and with patients with meal‐unrelated abdominal distention, patients with severe meal‐related abdominal distention show a significantly reduced recto‐sigmoid tone after meal, paralleling abdominal girth increase. Further studies are needed to evaluate whether drugs acting on the modification of intestinal tone could be useful in the treatment of these patients.